dari Reguler ke Revolusioner: Literasi Sains dalam Pembelajaran Fermentasi Berbasis Pjbl-Stream - Afifah, Syifa; Sukmawardani, Yulia; Agustina, Tri Wahyu (Universitas Negeri Surabaya, 2025)
According to the results of PISA 2022 in Indonesia, science literacy skills are currently very low. This study aims to describe the PjBL-STREAM model on fermentation material to improve students' science literacy, analyze the implementation, analyze the improvement of PjBL-STREAM and regular learning and describe students' responses to learning fermentation material with PjBL-STREAM learning and learning without STREAM. The method used in this study is Mixed methods with an embedded design research design type. The main data in this study is QUAN data regarding the improvement of students' science literacy, while the supporting data is QUAL data which is used as complementary data from quantitative research such as discussing the design of the PjBL-STREAM model, implementation and student responses. This study uses purposive sampling. The results of the study were that classes that studied using the PjBL-STREAM model experienced higher improvements than classes that studied without PjBL-STREAM with an N-gain value (0.51> 0.40). This success is also supported by the PjBL-STREAM model design which received validity from the three expert teams with a very high category, namely with a score of 0.87. The implementation in both classes produced a score of 100%. Student responses to PjBL-STREAM received higher scores than students who carried out learning without PjBL-STREAM. The success of this PjBL-STREAM learning model depends on the readiness of the teacher and the interests and motivation of the students.